Analisis Fenomena “Resource Curse” pada Daerah Pertambangan di Indonesia - Aldrina Febriani; Dicky Iranto; Riswandi Riswandi (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyse the impact of the mining sector’s contribution and Average Years of Schooling (AYS) on the growth of Regional Gross Domestic Product (RGDP), as well as the impact of the mining sector’s contribution and Local Revenue (PAD) on the Human Development (IPM). This quantitative study employs multiple linear regression on panel data (a combination of time series from 2011–2024 and cross-sectional data) across eight mining-producing provinces in Indonesia selected through a purposive sampling technique. Secondary data were sourced from official publications of the Central Statistics Agency (BPS) and the Directorate General of Budget and State Financial Management (DJPK) of the Ministry of Finance. The results indicate that the mining sector’s contribution has a positive and significant effect on GRDP growth; thus, no evidence of the resource curse was found in the context of economic growth. However, the mining sector’s contribution exhibits a negative and insignificant effect on the Human Development Index (HDI), indicating a tendency toward the “resource curse” phenomenon, as the economic benefits of mining have not yet been optimally converted into public welfare. On the other hand, RLS is found to have a positive and significant effect on GRDP growth, consistent with human capital theory. Local Revenue (PAD) also has a positive and significant effect on the Human Development Index (HDI), confirming that public welfare is greatly influenced by the effectiveness of local governments in managing fiscal capacity for public services, rather than relying solely on mining revenues.